Design of a Unit Department for the Administration and Execution of Technological and Innovation Projects: A Case Applied to Mechatronic Projects - Carlos Gabriel Díaz Saenz; Pablo Daniel Bonaveri; Gustavo Rodriguez Albor (Engineering Proceedings)
Currently, the administration of innovation and technology, and the execution of technological projects (in this case, mechatronic projects) is, for all types of organizations, a challenge that requires the use of the creativity and initiative of its professionals, investing or implementing processes, machines, products, and services in such a way that inventions, designs, and prototypes provide solutions to environmental problems and facilitate society. Therefore, in innovation projects, it should be considered that it corresponds not only to the application of new technologies, but also to the generation of an outcome that is useful for the objective, quantifiable, and productive segment, as applied to mechatronic projects. Therefore, it is necessary and relevant to carry out a process of orderly development in the following phases: identification of need, ideation, development, construction, and verification of the final solution of these mechatronic projects. The above is turned towards a comprehensive design process around the academy, which for the purposes of this research takes place at the Universidad Autónoma del Caribe, which, according to the indicators of technological development and innovation, is positioned among the top ten positions at a national level (over 350 measured universities) in the DTI-Sapiens ranking, published every two years since 2017 by the consulting firm Sapiens Research and recognized by the international IREG Observatory. The Unit Department for the Administration and Execution of Technological Projects and Innovation: A Case Applied to Mechatronic Projects aims to achieve a balanced technological offer in the universe of R&D&I projects in mechatronics, among economic and social scientific values. In this way, it will be possible to consolidate links with the socioeconomic environment for the transfer of existing knowledge in HEIs, its exploitation by stakeholders, and the increase in the development of R&D&I projects, strengthening capacities in the UEES relationship for the transfer of know-how to companies.